Dynamika mikroprzedsiębiorstw z uwzględnieniem podziału terytorialnego NUTS 2 - Dehnel, Grażyna (Small Business Demography for NUTS 2, 2009)
Demand for statistics on business demography has grown and developed considerably in recent years. The creation of new enterprises as well as their closure is one of important factors that show the market's capacity to respond to changing market conditions. Unfortunately, there is not much information on this important topic in Poland due to the lack of appropriate micro data on firms. The only business demography publication, based on the results of panel survey conducted for small firms, contains information on survival rates only for Polish Classification of Economic Activities cross-section. Therefore, the paper aims to provide some basic informations on enterprise birth, survival and deaths rates, as well as in the joint cross-section of Polish Classification of Economic Activities (PKD) and voivodships. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 408-417